Taking Stock, July 2013 : An Update on Vietnam's Recent Economic Developments - World Bank (Hanoi, 2013)
The global economy appears to be transitioning toward a period of more stable albeit moderate pace of growth. Global Gross Domestic Product (GDP), which slowed in mid-2012, is recovering and a modest acceleration in quarterly GDP is expected during the course of 2013. In the developing world growth remains solid, but there are some signs of easing. More than four years after the financial crisis started, global industrial output is only 5.3 percent higher than its pre-crisis peak. While the global financial market conditions continue to improve, eventual phasing out of quantitative easing in advanced economies is beginning to worry investors. The improvement in financial conditions can be seen in lower yields on long-term debt, higher stock market returns and near-record flow of gross capital to developing countries. Vietnam's economy is experiencing its longest spell of slow growth since the onset of economic reforms in the late-1980s. Real GDP grew by 5 percent in 2012, the lowest level since 1998. The economy extended its slow growth into the first half of 2013, registering a growth rate of 4.9 percent in the first quarter and 5 percent in the second quarter. This is the first time that Vietnam has experienced two consecutive years of sub-5 percent growth in the first half of the year since it started publishing quarterly GDP. In fact what had distinguished Vietnam from other countries is its ability to recover rapidly after an economic shock-be it during the East Asian crisis in 1999 or the global financial crisis in 2009. However, Vietnam has found it harder to take timely and decisive actions to jumpstart its economy from the current growth slowdown. Vietnam is the only large developing country in the East Asia and Pacific region other than China whose post-crisis growth rate has been lower than its pre-crisis level.